Relationship between m7G regulators and clinical factors - Jiangli Zhao (2308330) (2025)
(A) Clinical heat map including expression of m7G regulators of epilepsy patients. (B-E) Relationship between m7G score and age (B), gender (C), subtype of epilepsy (D), and drug-response (E). (F) Sankey diagram displaying relationship among three grouping methods. (PNG)